2020
DOI: 10.1155/2020/5176536
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rotation Speed on Microstructure and Mechanical Properties of Friction‐Stir‐Welded 2205 Duplex Stainless Steel

Abstract: In the present study, 1.86-mm-thick steel plates (UNS S32205) were friction-stir-welded at various rotation speeds of 300 to 600 rpm and a constant welding speed of 100 mm·min−1. The effect of rotation speed on the microstructure and mechanical properties of the welds was researched. The welding temperature was recorded during friction stir welding (FSW), and the microstructure and mechanical properties of the welds were assessed. The incomplete penetration defect was formed at 300 rpm due to the insufficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Under the welding parameters in the current study, the 2205 DSS were FSWed in the α and γ phases. The ferritization had not happened during the FSW process, and the slight range fluctuation of the α:γ ratio is likely to be a result of the original change in the ratio of the phases in DSS BM [29]. This result recommends FSW to weld DSS 2205 without changing in α and γ ratio at the suggested welding parameters in the current work.…”
Section: Ferrite Contentmentioning
confidence: 70%
See 1 more Smart Citation
“…Under the welding parameters in the current study, the 2205 DSS were FSWed in the α and γ phases. The ferritization had not happened during the FSW process, and the slight range fluctuation of the α:γ ratio is likely to be a result of the original change in the ratio of the phases in DSS BM [29]. This result recommends FSW to weld DSS 2205 without changing in α and γ ratio at the suggested welding parameters in the current work.…”
Section: Ferrite Contentmentioning
confidence: 70%
“…They remarked decreasing in grain size of the stir zone (SZ) for both α and γ phases with an increase in the welding speed. Wang et al [29] faced serious sticking problems in FSW of 1.86 mm 2205 DSS with tungsten-rhenium-based FSW tool at a constant travel speed of 100 mm/min with the range from 300 to 600 rpm rotational welding speeds. Incomplete penetration was detected at 300 rpm, and a groove-like defect was attained at the highest rotation speed of 600 rpm.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [40] found that the grain size (within SZ) decreases with the decreasing rotation speed due to the corresponding lower heat input. It can be concluded that the hardness values obtained within SZ can be interpreted by the fact that employing higher rotation speeds would result in both larger heat input (higher peak temperature), and higher strain rate (more intense deformation) [41], which act in an opposing way to determine the hardness. Comparing Figure 12b with Figure 12c, it is clear that the changes in hardness values in the SZ and TMAZ follow an almost similar trend in both IHT725 and IHT775 samples.…”
Section: Microstructural Characterization: Steel Hook and Sheet Micro...mentioning
confidence: 99%
“…As shown in equation ( 8), the tool rotational and maximum temperatures are directly related to one another. The researcher [28] propose a relation between peak temperature, tool rotation, welding speed, and melting temperature speed as shown in equation (8).…”
Section: The Influence Of Tool Rotational Speedmentioning
confidence: 99%